(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2024)
This article aims to describe the concept of character education management and educational methods based on the study of thematic hadith. This research is carried out with a qualitative approach through the literature study method. The main sources of data for this research are various scientific articles, research results, and reference books that are relevant to the focus of this research. Scientific articles come from various credible and valid journal sources and are indexed on the database on google scholar. Data analysis was carried out qualitatively consisting of data reduction, data presentation and conclusion drawing. The results of the data analysis show that the need for differentiated education for generation Z so that the learning or material taught can be conveyed and understood to good practice for generation Z. So that at every level of education, students get learning experiences that bring them changes for the better and make them as kamil people and can be applied in daily life. This approach can integrate religious education and character education in one curriculum. Students will better understand and internalize the value of religious values because they learn in an environment that is consistent with these values. Students will find it easier to implement the values taught in their daily lives because they live in the same environment as the school